Estilos de aprendizaje en estudiantes de la “Unidad Educativa Liceo Iberoamericano”. Riobamba - Ramos Martínez, Lizbeth Stephany (2025)
This research focused on analyzing the predominance of learning styles among fourth, fifth, and sixth – grade students in Basic General Education to determine the importance of this study in the need to personalize and optimize teaching processes for better academic performance bases on the use of appropriate methodologies and teaching strategies. Learning is an individual and continuous process; however, not everyone learns in the same way, as different learning styles influence how they process and assimilate information. Leaning styles manifest through behaviors, skills, habits, and experiences acquired by students throughout their academic training. They influence the way students process and acquire knowledge. Methodologically, the research adopted a quantitative approach with a non- experimental design. It is classified as descriptive and comparative, combining fieldwork with bibliographic time period, combining fieldwork with bibliographic and documentary review. A psychologist technique was employed using the learning Channel Test by Lynn O´Brien. Based on the results obtained, it was determined that the predominant learning style among basic education students is the visual style, suggesting the importance of implementing and utilizing a variety of appropriate teaching strategies and methodologies to achieve improvements in students’ academic performance.